Osteology and functional morphology of a transitional pterosaur Dearc sgiathanach from the Middle Jurassic (Bathonian) of Scotland - Natalia Jagielska; Michael O’Sullivan; Ian B. Butler; Thomas J. Challands; Gregory F. Funston; Dugald Ross; Amelia Penny; Stephen L. Brusatte (BMC Ecology and Evolution)
Abstract Pterosaurs were the first vertebrates to evolve active flight. The lack of many well-preserved pterosaur fossils limits our understanding of the functional anatomy and behavior of these flight pioneers, particularly from their early history (Triassic to Middle Jurassic). Here we describe in detail the osteology of an exceptionally preserved Middle Jurassic pterosaur, the holotype of Dearc sgiathanach from the Isle of Skye, Scotland. We identify new autapomorphies of the flight apparatus (humerus and sternum), which further support the distinctiveness of Dearc compared with other early-diverging pterosaurs and describe features, such as the vertebral morphology, shared with later-diverging pterosaurs that probably developed convergently to support a large body size or as a sign of modular evolution. We used extant phylogenetic bracketing to infer the principal cranial and antebrachial musculature, indicating that Dearc had large and anteriorly placed palatal musculature that compensated for weak temporal jaw adductors and wing musculature suggestive of flight style reliant on powerful adduction and protraction of the humerus. Comparisons with other pterosaurs revealed that non-pterodactyloids such as Dearc, despite their overall conservative bauplans, adapted various flight and feeding styles. The osteology and myology of Dearc are indicative of a large predator that flew and hunted above lagoons and nearshore environments of the Middle Jurassic.